Building a structural model for evaluating financial performance in commercial banks - A study of a group of Algerian banks for the period between 2005-2019 - bendjeddou, Amina; mihoub, Messaoud (Journal of Research in Finance and Accounting, 2021)
The study aims to build a structural model to carry out the process of evaluating the financial performance of commercial banks, by relying on the financial statements of a group of Algerian banks for the period between 2005-2019, using exploratory and confirmatory factor analysis. It was concluded in this research paper that the Algerian commercial banks follow the traditional pattern in their business process, as they rely mainly on debt, and specifically on deposits, to increase their liquidity, as well as employ this liquidity in order to achieve profits, allowing in parallel to provide the necessary security.